Effect of surface hydrophilic modification on the wettability, surface charge property and separation performance of PTFE membrane. (December 2015) - Wang, Feng; Zhu, Hailin; Zhang, Huapeng; Tang, Hongyan; Chen, Jianyong; Guo, Yuhai
Abstract: In order to expand application of polytetrafluoroethylene (PTFE) membrane in water process engineering, the wettability and antifouling property of PTFE membrane were studied in this work. Firstly, hydrophilic agents including amino (NH2 ), carboxyl (COOH) and sulfonic acid (SO3 H) groups, as different hydrophilic groups, are synthesized via hydrolytic polycondensation and free radical polymerization, which were further steadily adhered to the surface of PTFE membrane by a facile physical entanglement method. Effect of hydrophilic groups on the membrane surface morphology, chemical composition, membrane characteristics and surface charge property was studied. Furthermore, filtration performance was evaluated using a bovine serum albumin (BSA) wastewater and ink as feed solutions in microfiltration. The results indicate that hydrophilic agents are firmly adhered to membrane surface due to a mechanical interlocking, which provides the excellent hydrophilicity and remits the hydrophobic interaction between the bare PTFE membrane and BSA protein molecules in microfiltration. In addition, membrane surface zeta potential alters after hydrophilic modification, leading to the stronger electrostatic repulsion between the bare PTFE membrane and BSA protein molecules. Therefore, antifouling property is finally enhanced by the synergistic effect between the ameliorative wettability and stronger electrostatic repulsion, which decreases the flux decay rate and improves the flux recovery. We hope such hydrophilic PTFE membrane modified by a simple physic entanglement method could be potentially useful in separation field.